2008
DOI: 10.1590/s0100-72032008001100006
|View full text |Cite
|
Sign up to set email alerts
|

Interferência da idade sobre a qualidade seminal

Abstract: XLSTAT (p<0,05). RESULTADOS: os indivíduos estudados tinham média de idade de 37±7,9 anos, com um volume seminal médio de 3±1,4 mL, uma concentração espermática de 61,4±66,4 espermatozóides por mL de sêmen, motilidade progressiva de 44,7±19,4% do total de espermatozóides e morfologia normal de 11,2±6,6% dos espermatozóides. As médias de idade entre os grupos foram semelhantes, exceto a média dos indivíduos com hipoespermia, que foi significativamente maior que a dos homens com normoespermia (39,6±10,3 versus 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
1
7
1
1
Order By: Relevance
“…Berling and Wolner-Hanssen (1997) study that analysed 718 infertile Swedish men for a period of 10 years reports insignificant decrease in semen volume and increase in morphology and motility, thereby fails to establish a correlation between age and semen parameters [43]. A most recent study showed an inverse effect of age on semen volume, but not on other semen parameters [42]. This ambiguous relationship between age and changes in semen features are also observed in our study subjects.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Berling and Wolner-Hanssen (1997) study that analysed 718 infertile Swedish men for a period of 10 years reports insignificant decrease in semen volume and increase in morphology and motility, thereby fails to establish a correlation between age and semen parameters [43]. A most recent study showed an inverse effect of age on semen volume, but not on other semen parameters [42]. This ambiguous relationship between age and changes in semen features are also observed in our study subjects.…”
Section: Discussioncontrasting
confidence: 61%
“…Several reports demonstrated the inverse relationship between age and the semen parameters [33,35], on contrary other studies showed the negligible influence of age on various semen characteristics [34][35][36]42]. For example, Kidd et al, (2001) suggested that advanced age is associated with a decrease in semen volume, sperm motility, and sperm morphology, but has no effect on sperm count [30].…”
Section: Discussionmentioning
confidence: 99%
“…A recent review has found it difficult to find in the literature a clear relationship between increased paternal age and sperm concentration 24 . Azoospermic individuals were older than normozoospermic ones, however, when compared, the average ages did not present significant differences 25 . However, in the present analysis, the azoospermia group had a significantly higher average age than the normozoospermia group, suggesting a decrease in concentration with increasing age.…”
Section: Graph 2 -Number Of Individuals Assisted In Reproduction Clinmentioning
confidence: 71%
“…There are many studies that focus on the correlation between age and male / female infertility, all of them concluding that advanced paternal age is a strong risk factor of disorders that include production and sperm quality (CAVALCANTE et al 2008, [5]). Although there is no age limit for male fertility, studies reveal that fertility starts to decline at the age of 40 (TELÕKEN et al 1999, [33]).…”
Section: Figure 2 Distribution Of Patients Belonging To Different Agmentioning
confidence: 99%
“…(AITKEN et al 1995, [3]; PASQUALOTTO et al 2011, [4]). Factors such as urogenital infections, exposure to toxic substances and vascular diseases may impair seminal quality, resulting in embryonic defects, loss of pregnancy or children highly prone to develop genetic diseases and other pathologies (CAVALCANTE et al 2008, [5]). The correct estimation of male fertility potential has become of great interest to researchers, but available tests are not always accurate for this specific pathology.…”
Section: Introductionmentioning
confidence: 99%